Effects of micro-environmental factors on the photoautotrophic growth of Hibiscus sagittifolius Kurz cultured in vitro - Phuong Duyen, Nguyen Thuy; Van, Tran Thi; Le Minh, Nguyen Thu; Quynh, Nguyen Thi (Academia Journal of Biology, 2018)
The arrow leaf abelmoschus rhizome (Hibiscus sagittifolius Kurz), or Sam Bo Chinhin Vietnamese, is a perennial suffrutex herb from which the tuber root is used as a medicine in folk remedy. This species is widely distributed and can be found on many terrains across South East Asia. With an aim to create a large number of uniform and high-quality H. sagittifolius transplants in vitro, effects of some environmental factors such as photoperiod and temperature on the photoautotrophic growth of H. sagittifoliusin vitro plants were investigated. In vitro single nodal cuttings, each with an unfolded leaf, were cultured photoautotrophically (without sucrose and vitamins) on mineral SH medium, under light intensity of 150 µmol m-2 s-1, temperature of 24oC ± 2oC, relative humidity (RH) of 55% ± 5% and three different photoperiods (8, 12 or 16 h d-1) in the first experiment. Commercial polypropylene bags (V = 1,000 ml), attached with two filter-paper membranes, were used as culture vessels. After 42 days of culture, H. sagittifolius plants under the photoperiod of 16 h d-1 had the greatestincreased fresh weight (502.3 mg/plt), increased dry weight (39.5 mg/plt) and leaf area (17.0 cm2) than those put under 8 hd-1or 12 h d-1. In addition, H. sagittifolius plants also showed statistical differences in growth when photoautotrophically cultured in different air temperature regimes, including 28/25oC (photo-/dark period), 25/25oC and 20/25oC. Increased fresh weight (775 mg/plt), increased dry weight (62 mg/plt) and leaf area (22.7 cm2) of in vitro H. sagittifolius plants were the greatest when temperature was maintained at 28 oC during photoperiod. On the contrary, the photoperiod temperature of 20oC resulted in the shortest shoot length and root length of H. sagittifoliusplants. In conclusion, this study proved that H. sagittifolius plants had the best growth when cultured on SH medium, without sucrose and vitamins supplementation, under light intensity of 150 µmol m-2 s-1, RH 55% ± 5%, photoperiod of 16 h d-1, temperature regime of 28/25oC(photo-/dark period). Citation: Nguyen Thuy Phuong Duyen, Tran Thi Van, Nguyen Le Thu Minh, Nguyen Thi Quynh, 2017. Effects of micro-environmental factors on the photoautotrophic growth of Hibiscus sagittifolius Kurz cultured in vitro. Tap chi Sinh hoc, 39(4): 496-506. DOI: 10.15625/0866-7160/v39n4.11030. *Corresponding author: qtnguyen_vn@yahoo.comReceived 7 September 2017, accepted 15 December 2017